CRISPR/Cas9-Based Editing of Streptomyces for Discovery, Characterization, and Production of Natural Products - Tao, Weixin; Yang, Anna; Deng, Zixin; Sun, Yuhui (Frontiers in Microbiology, 2018)
Microbial natural products (NPs) especially of the Streptomyces genus, have been regarded as an unparalleled resource for pharmaceutical drugs discovery. Moreover, recent progress in sequencing technologies and computational resources further reinforces to identify numerous NP biosynthetic gene clusters (BGCs) from the genomes of Streptomyces. However, the majority of these BGCs are silent or cryptic in native strains and remain to be investigated and activated, which relies heavily on efficient genome editing approaches. Accordingly, numerous strategies are developed, especially, the most recently developed, namely clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR associated (Cas) system reveals remarkable higher accuracy and efficacy for genome editing in various model organisms including the Streptomyces. In this mini-review, we highlight the application of CRISPR/Cas9-based approaches in Streptomyces, focus on the editing of BGCs either in vivo or in vitro, as well as target cloning of large-sized BGCs and heterologous expression in a genetically manipulatable host, for discovery, characterization, reengineering, and production of potential pharmaceutical drugs.